HUMAN RIGHTS AND ASIAN VALUES - Stević, Ljiljana Z (Politeia, 2019)
This paper presents the importance of issue of universality of human rights and relations towards Asian values i.e. Confucianism. Abstract ideas on inherent existence of rights for all human beings are the key reason why human rights are possessed by all people hence universality. On the other hand, universality does not equal uniformity. Application of human rights and freedom is the product of historical experiences of certain people hence it is different in different cultural and political communities. The paper first tackles the issue of universality of human rights. In central part it presents Confucianism and human rights and issue of human rights in China. In the conclusion it emphasizes necessity to incorporate Asian values in the western concept of human rights as well as the need for more flexible communities and accepting ideas from different contexts.